موضوعة الوطن وأصولها الدينية في الخطاب الشعري القديم -نماذج مختارة - خلوي, شميسة (جامعة الوادي - university of Eloued, 2021)
لقد عمرت الدنيا بحب الأوطان، هذا الحب الذي يعد غريزة متأصِّلة في نفوس البشر، وإننا نروم من خلال هذه الورقة البحثية بسط الحديث عن ثيمة الوطن وتجلياتها في الشعر العربي القديم على أن نجسِّر العلاقة بين المنجز الشعري والأصول الدينية التي استقى منها الشعراء معانيهم، فثيمة الوطن لها امتداد عبر ثيمات ثانوية كانت حاضرة في مدركات الشاعر الدينية والتي جسَّدها قريظا، بين مشاعر وأحاسيس وأقوال وأفعال، على شاكلة حب الوطن والحنين إليه، والدعاء له، والاستشفاء بتربته، والرباط فيه، وعمارته ودا بحب المواطنين بعضهم بعضا وذلك بالتزاور وحُسن الجوار وغير ذلك، وتأسيسا على ما سبق، كان منهجنا هو ذكر الموضوعة ثم ما ورد بشأنها من أصول دينية ثم رصد نماذج شعرية قديمة تتناول نفس الموضوعة. الكلمات المفتاحية: الوطن؛ الشعر العربي القديم؛ المنهج الموضوعاتي؛ الخطاب الديني. Abstract: The world has been filled with love of homelands, this love which is an instinct inherent in the souls of human beings, and we aim through this research to simplify the discussion about the homeland and its manifestations in ancient Arabic poetry, on the condition that we link the relationship between the poetic achievement and the religious origins from which the poets brought their meanings. The issue of the homeland has an extension through secondary topics that were present in the poet's religious knowledge, which he embodied as a combination of feelings, words and actions, in the form of love for the country and longing for it, praying for it, healing with its soil, attachment to it, and filling it with the citizens' love for each other by visiting one another, good neighborliness, etc. Based on the above, our approach was to mention the aforementioned idea, then the religious origins that came about it, and then bring old poetic models that deal with the same mentioned idea. key words: The homeland; old Arabic poetry; the thematic approach; religious speech.
مقال
Keywords: الشعر العربي القديم; الخطاب الديني; الوطن; المنهج الموضوعاتي